The incorporation of acetylated LAP-TGF-[beta]1 proteins into exosomes promotes TNBC cell dissemination in lung micro-metastasis - Yu, Pei; Han, Yubao; Meng, Lulu; Tang, Zengying; Jin, Zhiwei; Zhang, Zhenzhen; Zhou, Yunjiang; Luo, Jun; Luo, Jianguang; Han, Chao; Zhang, Chao; Kong, Lingyi (Molecular cancer, 2024)
Triple-negative breast cancer (TNBC) stands as the breast cancer subtype with the highest recurrence and mortality rates, with the lungs being the common site of metastasis. The pulmonary microenvironment plays a pivotal role in the colonization of disseminated tumor cells. Herein, this study highlights the crucial role of exosomal LAP-TGF-[beta]1, the principal form of exosomal TGF-[beta]1, in reshaping the pulmonary vascular niche, thereby facilitating TNBC lung metastasis. Although various strategies have been developed to block TGF-[beta] signaling and have advanced clinically, their significant side effects have limited their therapeutic application. This study demonstrates that in lung metastatic sites, LAP-TGF-[beta]1 within exosomes can remarkably reconfigure the pulmonary vascular niche at lower doses, bolstering the extravasation and colonization of TNBC cells in the lungs. Mechanistically, under the aegis of the acetyltransferase TIP60, a non-canonical KFERQ-like sequence in LAP-TGF-[beta]1 undergoes acetylation at the K304 site, promoting its interaction with HSP90A and subsequent transport into exosomes. Concurrent inhibition of both HSP90A and TIP60 significantly diminishes the exosomal burden of LAP-TGF-[beta]1, presenting a promising therapeutic avenue for TNBC lung metastasis. This study not only offers fresh insights into the molecular underpinnings of TNBC lung metastasis but also lays a foundation for innovative therapeutic strategies.